MENGEMBANGKAN MODEL KELEMBAGAAN PEMERINTAHAN DAERAH, MENYIKAPI LIMA TAHUN PERJALANAN OTONOMI DAERAH DI INDONESIA - Wibowo, Eddy Kusponco (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2005)
Five years of local autonomy implementation has passed since the release of Law No. 22 Year 1999. Surprisingly, during the five-year implementation, the performance wasmnot as expected by its stakeholders. The local autonomy should be managed and,implemented in proper, concurrent, consistent, simultaneous and sustainable manners.,Based on the perspective of the organizational development of local government, the,main problem of local autonomy encompasses the weaknesses in developing three mainstrategies: structural, behavioral, and technical strategies, which lie within the regional,government itself. These weaknesses contribute to the poor performance in regional,autonomy management. To strive for the success of the regional autonomy, regional,governments have to raise their competitive advantage. The local governments may,acquire the competitive advantage when they are able to develop their knowledge in a,systematic and continuous way. This will result in their competitive strategy in the,field of product innovations, services, and organizational processes. To acquire,competitive advantage capabilities, local governments should empower their key,enablers through the local government organizations. By doing so, it is expected that the aim of local autonomy can be accomplished.